Analyzing ecological environment change and associated driving factors in China based on NDVI time series data. (October 2021) - Jiang, Luguang; Liu, Ye; Wu, Si; Yang, Cheng
Graphical abstract: Highlights: Accurate assessment of China's ecological environment changes in the past 20 years is important. We used time-series NDVI data (1998–2018) to evaluate China's ecological environment change. In one-third of China the ecological environment has improved, and in 10%, the ecological environment has deteriorated. The Yellow River Basin is an area where the ecological environment has significantly improved. The main reason for the deterioration in the ecological environment of the eastern coastal areas is urban expansion. Abstract: The ecological environment is the foundation of human survival and development. China's ecological environment has undergone a historic transition from partial improvement to overall improvement. In this paper, long time series NDVI data (1998–2018) are used to evaluate the ecological environment change and spatiotemporal change that has taken place in China over the last 20 years, at different scales (regional, provincial, county, and grid scales). Combined with typical areas, the causes of ecological environment change are revealed. The results show that in about one-third of China, the ecological environment improved, and in 10%, the ecological environment deteriorated. Ningxia, Shaanxi, Shanxi, Guizhou, and Guangxi are the provinces in which the improvement of the ecological environment is most pronounced. However, the ecological environments with vegetation as the core in Shanghai and Jiangsu Province have deteriorated significantly. The areas with the fastest improvement in their ecological environment are those with precipitation of 200–600 mm. The Yellow River Basin is an area where the ecological environment has significantly improved. Forestry projects and the development of oasis agriculture effectively promote the improvement of the ecological environment. In the past 20 years, the main reason for the degradation of the ecological environment in eastern coastal areas is urban expansion. China should continue to strengthen its overall layout of forestry projects and improve its ecological environment. When planning its ecological construction, China should fully consider the associated physical and geographical conditions, and adjust measures to local conditions accordingly. China should coordinate the relationship between development and protection and avoid the "pie spread" expansion witnessed in eastern coastal areas.